Does Electronic Payment Services Create Value to Bank Performance? Evidence from Southeast Asia - Lu, Ming Pey; Ooi, Chai-Aun; Lee, Kian Tek; Kossim, Zunarni (Asian Academy of Management Journal of Accounting and Finance, 2022)
This study examines the nexus between four electronic payment channels’ transaction values and bank performance of Malaysia, Singapore and Thailand for 2010–2020. We find that, the impact of credit and charge card’s transaction value on banks’ return on equity (ROE) is significantly positive across various econometric specifications, including firm fixed effect panel regression, two-way clustering method and generalised method of moment. Instead, the impacts of the other three payment channels (e-money, debit card and internet and mobile banking) are negative but not significance across all econometric specification. These suggest that only the credit and charge card is economically relevant to the banks’ shareholders. We further add that only credit and charge card significantly improves banks’ operating income, while all four payment channels are not significantly related to revenue growth of the banks. In the additional analysis, we find that e-money, debit card, internet and mobile banking are negatively influencing the relationship between banks’ operating income and ROE. In summary, our study implies that majority of the electronic payment services offered by banks are not economically sustainable in the long run.